A three-stage assembly flow shop scheduling problem with blocking and sequence-dependent set up times - Aref Maleki-Darounkolaei; Mahmoud Modiri; Reza Tavakkoli-Moghaddam; Iman Seyyedi (Journal of Industrial Engineering International, 2012)
This paper considers a three-stage assembly flowshop scheduling problem with sequence-dependent setup times at the first stage and blocking times between each stage in such a way that the weighted mean completion time and makespan are minimized. Obtaining an optimal solution for this type of complex, large-sized problem in reasonable computational time using traditional approaches or optimization tools is extremely difficult. Thus, this paper proposes a meta-heuristic method based on simulated annealing (SA) in order to solve the given problem. Finally, the computational results are shown and compared in order to show the efficiency of our proposed SA.
Keywords: 650; assembly flowshop scheduling; sequence-dependent setup times; blocking times; weighted mean completion time; makespan; Simulated annealing